Strategic Supply Chain Management : the Development of a Diagnostic Model - Sindi, Safaa; Roe, Michael (Cham: Palgrave Macmillan, 2017)
This book analyses the development of strategic supply chain modelling and its role in optimising decision-making in business, in relation to advances in technology and increased demand due to globalisation. The authors examine existing supply chain models in order to create a conceptual framework for a new diagnostic model, offering a useful, realistic and meaningful contribution to the field, both theoretically and practically. Using the real-life context of a major international automobile manufacturer, this study satisfies the demand from industry for guidance in the complex world of strategic supply chain modeling in the growing logistics business sector. Readers of Strategic Supply Chain Management will find this work instructive and informative, and it will be of particular interest to students, researchers and policy-makers in the supply chain management industry.
1. Introduction to Strategic Supply Chain Modelling -- 2. The Evolution of Supply Chains and Logistics -- 3. A Theoretical and Conceptual Framework for Strategic Supply Chains -- 4. A Methodology for the Strategic Supply Chain Model -- 5. Data Collection for Strategic Supply Chain Modelling -- 6. The Application of Fuzzy Delphi to Strategic Supply Chain Modelling -- 7. Data Analysis for Strategic Supply Chain Modelling -- 8. Testing and Implementing the Strategic Supply Chain Model -- 9. Conclusions: What Next for Strategic Supply Chain Modelling.
Keywords: Automobile industry and trade; Business logistics; International business enterprises; Organization; Planning; Supply Chain Management; Automotive Industry; International Business; Logistics; Organization